Dimensional Changes of Red Dragon Fruit (Hylocereus Polyrhizuz) Slices During the Drying Process - Putri Sejagat, Laradita; Muhidong, Junaedi; Salim, Iqbal; Yumeina, Diyah (Salaga Journal, 2023)
Dragon fruit is one of the fruits with a fairly high water content which causes an increase in water activity and accelerates the growth rate of microorganisms. research was conducted to determine the shrinkage that occurs in the fruit. Two different sample sizes were used in this study. Both were cylindrical in shape with a diameter of 2.5 cm and different lengths. 3 cm (Sample A) and 1.5 cm (Sample D). The number of samples used for sample A and sample D was 5 pieces each. Measurements of weight and dimensions (sample length and diameter) were repeated every 15 minutes during the drying time at 45 ºC. Once the sample weight was constant, the material was put back into the oven at 105 ºC for 72 hours. After 72 hours, the sample was weighed and measured to determine the dry weight of the sample. Based on the study of the pattern of changes in the dimensions of red dragon fruit during the drying process, it can be concluded that the pattern of changes in volume ratio to KAbb is a linear pattern with an R2 value of 0.9946. The pattern of changes in volume ratio to KAbb is polynomial degree 2 and 3, but the R2 value is greater for degree 3, so degree 3 is more suitable for estimating the volume ratio of KAbb.values.